1973
DOI: 10.1021/ic50124a034
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectra of some xenon(II) compounds1

Abstract: which the color changed from orange to green-brown. The solvent was removed by rotary evaporation and the residual oil was redissolved in 250 ml of distilled water. The aqueous solution was extracted with four 125-ml portions of benzene and then added to a solution of 5 g tetramethylammonium chloride in 25 ml of water. The cloudy solution was clarified by the addition of 50 ml of acetone and then rotary-evaporated to a volume of about 25 ml by which time the formation of black crystals had occurred. The crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
3
2

Year Published

1973
1973
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 5 publications
3
40
3
2
Order By: Relevance
“…The band at higher frequency is labeled as the short-bond Xe}F stretch ( (Xe}F)), and that at lower frequency as the long-bond Xe}F stretch ( (Xe2F)). It has previously been concluded that the stretching frequency for (Xe}F)> should be at or higher than 600 cm\ (28). From the structure of the 1:2.5 compound the XeF molecules that are uniquely bound to Nd> are seen to be distorted and on the ionization pathway.…”
Section: Raman Spectra Ofmentioning
confidence: 96%
“…The band at higher frequency is labeled as the short-bond Xe}F stretch ( (Xe}F)), and that at lower frequency as the long-bond Xe}F stretch ( (Xe2F)). It has previously been concluded that the stretching frequency for (Xe}F)> should be at or higher than 600 cm\ (28). From the structure of the 1:2.5 compound the XeF molecules that are uniquely bound to Nd> are seen to be distorted and on the ionization pathway.…”
Section: Raman Spectra Ofmentioning
confidence: 96%
“…The polar-covalentb onds of NgF 2 (Ng = Kr or Xe) render both compounds fluoridei on donors towards strong Lewis acid pentafluorides such as AsF 5 ,S bF 5 ,B iF 5 ,N bF 5 ,T aF 5 ,a nd AuF 5 , and are customarily formulated as [NgF] + and [Ng 2 F 3 ] + salts, for example, [XeF][MF 6 ]( M= As, [1] Sb, [1] Bi, [1] Ru, [2] ), [XeF][M 2 F 11 ] (M = Sb, [1,3,4] Bi, [1] Ir, [5] Nb, [6] Ta [6] ), [XeF] 2 [Ti 9 F 38 ], [7] [XeF] [IrSbF 11 ], [5] [Xe 2 F 3 ][MF 6 ]( M = Au, [8] As, [9] Sb [9] ), [Xe 2 F 3 ][Ti 8 F 33 ], [7] [KrF] [MF 6 ] (M = Au, [8,10] Ta, [11] Pt, [12] As, [13] Sb, [11,13] Bi [13] ), [KrF][M 2 F 11 ]( M= Ta, Nb, Sb), [11] [Kr 2 F 3 ][SbF 6 ]·KrF 2 , [13] [Kr 2 F 3 ] 2 [SbF 6 ] 2 ·KrF 2 , [13] 6 ], [13] [KrF][PF 6 ], [13] and [Kr 2 F 3 ][PF 6 ]·nKrF 2 . [13] Althought heir formulationsi mply completef luoridei on transfer from the noble-gas difluoride to the strong Lewis acid pentafluoride, in reality the Lewis acidic [NgF] + cations and their anionse xist as ion pairs in their salts that interact through NgÀF b ---Mb ridges (F b :b ridge fluorine atom).…”
Section: Introductionmentioning
confidence: 99%
“…AV 2 F 11 (A = K, Cs) [60], CsTa 2 F 11 [64,65] and CsBi 2 F 11 [60] have been characterized only by vibrational spectroscopy.…”
Section: Am 2 F 11 Compoundsmentioning
confidence: 99%